Nonsuperneutrality of Money in the Sidrauski Model with Heterogeous Agents - Burkhard Heer (Center for Economic Studies and ifo Institute (CESifo), 2003)
Superneutrality is demonstrated to no longer hold in the Sidrauski model as soon as agents are heterogenous with regard to their productivity. However, quantitative effects of inflation on the capital stock are found to be rather small.
Keywords: 330; superneutrality; Sidrauski model; income heterogeneity